Sedimentary Black Carbon Isotope Record of Holocene Climate Changes on the Northeastern Tibetan Plateau. Issue 8 (15th August 2022) - Ning, Dongliang; Jiang, Qingfeng; Ji, Ming; Zheng, Jianan; Kuai, Xiang; Ge, Ying; Xu, Yuchen; Cheng, Longjuan; Zhao, Wenwei
Abstract: The northeastern Tibetan Plateau (TP) is an unique area for studying the interactions between the Asian Monsoonal climate and the westerlies. However, significant contraries on Holocene paleoclimate evolution are still exist. To better understand the climate history on the northeastern TP particularly its variability, we here investigated the stable carbon isotope compositions of Black Carbon (BC) (δ 13 CBC ) in Lake Gyaring sediment core from the source area of the Yellow River. The δ 13 CBC values were relatively positive before ∼6.2 cal kyr BP indicating that the climate on northeastern TP was warm and dry during the first half of the Holocene, while the decreasing trend thereafter reflects that the climate on the northeastern TP has become generally cooler and wetter since the middle Holocene. Superimposed on the long‐term paleoclimate evolution pattern, at least seven centennial‐scale cold‐wet events characterized by significant δ 13 CBC depletions occurred at about 8.4, 7.5, 6.2, 5.0, 4.3, 2.7, and 0.9 cal kyr BP. Those abrupt climate events well corresponded to the weak Asian Monsoon episodes and the ice‐rafted debris records in the North Atlantic. We speculate that the cold climate signals from the North Atlantic resulted from the sea‐ice expansion have been transported to the northeastern TP through the westerlies leading to a cold conditions there. Besides, the anomalous easterly water vapor transportation over the northern periphery of the TP during weak monsoon intervals has generated the wet conditions on the northeastern TP. Plain Language Summary: Understanding the hydroclimate changes on the Tibetan Plateau will contribute a lot to sustain the socioeconomic stability. However, very scarce studies focusing on the short‐term time scale climate variabilities from this area limit our knowledge on the spatial‐temporal pattern of abrupt climate changes and the underlying mechanisms. Here, we present a lacustrine record from the source area of the Yellow River to investigate the centennial‐scale climate oscillations on the northeastern TP. Our results reveal that at least six cold and wet events occurred during the Holocene. This is dramatically different from previous studies which indicate that abrupt climate fluctuations on northeastern TP have been characterized by cold and dry. Furthermore, all those events correspond well with the weak EASM episodes and the cold North Atlantic events. We suggest that the cold climate condition on the northeastern TP during those events could be related to the cold air mass transportation from the North Atlantic by the westerlies while the wet conditions should be related to the anomalous easterly water vapor transportation over the northern periphery of the TP during weak EASM intervals. Those findings provide new insights to understand the driving mechanisms of the climate oscillations on the northeastern TP. Key Points: The paleoclimate on the northeastern Tibetan Plateau is rather unstable during the Holocene Seven centennial‐scale climate oscillations occurred at about 8.4, 7.5, 6.2, 5.0, 4.3, 2.7, and 0.9 cal kyr BP The North Atlantic cold events have primarily controlled the climate fluctuations on the northeastern TP